Effect of preoperative two‐dimensional animation information on perioperative anxiety and knowledge retention in patients undergoing bowel surgery: a randomized pilot study. (25th April 2013) - Tou, S.; Tou, W.; Mah, D.; Karatassas, A.; Hewett, P.
Abstract Aim The use of multimedia information provided preoperatively can potentially reduce anxiety in patients and improve the hospital experience. However, the use of two‐dimensional (2D) animation (cartoon) to provide information to patients undergoing colorectal surgery has not been investigated. This study investigated the effect of preoperative 2D information on anxiety and knowledge retention in patients undergoing bowel surgery. Method Patients were randomized to one of two groups; the video group watched a 13‐min cartoon animation whereas the nonvideo group did not. Anxiety levels were measured at the preadmission clinic, postvideo, on the day of admission for surgery, within 24‐h after surgery and before discharge using the Spielberger state‐trait anxiety inventory and visual analogue scale. Both groups completed a knowledge retention questionnaire and the video group completed a feedback questionnaire about the animation. Results Thirty‐one patients (16 video, 15 nonvideo) participated in the study. There was no significant difference in baseline anxiety score between two groups. An immediate reduction (P = 0.03) in anxiety score was observed in the video group after watching the video compared with baseline. There was a significant reduction in anxiety score in the video group at discharge compared with the nonvideo group (P = 0.03). There was no significant difference in knowledge retention between two groups. Eighty‐eight per cent of patients who watched the video found it beneficial. Conclusion 2D animation is an effective medium for delivering information to patients undergoing bowel surgery and can potentially reduce anxiety related to surgery and improve the hospital experience.